ATF3 Stimulates IL-17A by Regulating Intracellular Ca2+/ROS-Dependent IL-1β Activation During Streptococcus pneumoniae Infection - Lee, Seungyeop; Kim, Gyu-Lee; Kim, Na Young; Kim, Se-Jin; Ghosh, Prachetash; Rhee, Dong-Kwon (Frontiers in Immunology, 2018)
Activating transcription factor-3 (ATF3) in the ER stress pathway induces cytokine production and promotes survival during gram-positive bacterial infection. IL-17A is a critical cytokine that is essential for clearance of Streptococcus pneumoniae. However, the mechanism by which ATF3 induces IL-17A production remains unknown. Here, we show that ATF3 induces IL-17A production via NLRP3 inflammasome-dependent IL-1β secretion. Survival rates were comparable in IL-17A-depleted and ATF3 KO mice but were lower than in WT mice treated with isotype control, indicating that ATF3 positively regulated IL-17A production. Indeed, ATF3 KO mice showed a marked reduction in IL-17A protein and mRNA expression compared to levels in WT mice. Moreover, mitochondrial IL-1β production by bone marrow-derived macrophages was significantly reduced in ATF3 KO mice as a result of the disruption of cellular ROS and Ca2+ homeostasis. Accordingly, ATF3 KO mice displayed diminished survival and bacterial clearance following S. pneumoniae infection. Taken together, these data suggest a mechanism in which macrophage ATF3 promotes IL-17A production in γδ T cells to rapidly induce host defenses during early S. pneumoniae infection.